2022
DOI: 10.3390/biomedicines10092067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes and Pathways in Genotoxic Stress Induced Endothelial Dysfunction: Results of Whole Transcriptome Sequencing

Abstract: Atherosclerosis is a leading cause of cardiovascular morbidity and mortality worldwide. Endothelial disfunction underlying the atherogenesis can be triggered by genotoxic stress in endothelial cells. In the presented research whole transcriptome sequencing (RNA-seq) of human coronary artery (HCAEC) and internal thoracic artery (HITAEC) endothelial cells in vitro exposed to 500 ng/mL mitomycin C (treatment group) or 0.9% NaCl (control group) was performed. Resulting to bioinformatic analysis, 56 upregulated dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…This task requires large amounts of ATP to rearrange the intercellular junctions and maintain intracellular Ca 2+ metabolism, which is also indispensable for the enzymatic digestion and biosynthesis of nitric oxide and prostacyclin, the potent vasodilators [121][122][123][124]. With regards to nucleotide metabolism, DNA repair defects have been associated with age-related and premature endothelial dysfunction which develops as reduced nitric oxide release and chronic low-grade inflammation [125][126][127][128][129][130][131]. The same has been reported for decreased ubiquitination and impaired autophagy, as removal of dysfunctional organelles, supramolecular complexes, and molecules also becomes compromised with age [132][133][134], and ubiquitination participates in regulating rearrangements of intercellular junctions and integrity of the endothelial barrier [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…This task requires large amounts of ATP to rearrange the intercellular junctions and maintain intracellular Ca 2+ metabolism, which is also indispensable for the enzymatic digestion and biosynthesis of nitric oxide and prostacyclin, the potent vasodilators [121][122][123][124]. With regards to nucleotide metabolism, DNA repair defects have been associated with age-related and premature endothelial dysfunction which develops as reduced nitric oxide release and chronic low-grade inflammation [125][126][127][128][129][130][131]. The same has been reported for decreased ubiquitination and impaired autophagy, as removal of dysfunctional organelles, supramolecular complexes, and molecules also becomes compromised with age [132][133][134], and ubiquitination participates in regulating rearrangements of intercellular junctions and integrity of the endothelial barrier [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…308K-05a, Cell Applications Inc., San Diego, CA, USA) cryopreserved at the 2nd passage were used in the present research. All manipulations with cells were performed as described previously [27]. Briefly, the cells were seeded into fibronectin-coated T-75 flasks (Greiner Bio-One GmbH., Kremsmünster, Austria) containing 15 mL of a Human MesoEndo Cell Growth Medium (Cell Applications Inc., San Diego, CA, USA) and incubated in a humidified atmosphere with 5% CO 2 at 37 • C. After 3 passages, the cells were reseeded into new T-75 flasks (Greiner Bio-One GmbH., Kremsmünster, Austria) and refed (after reaching 80% confluency) with another 15 mL of a Human MesoEndo Cell Growth Medium (Cell Applications Inc., San Diego, CA, USA) containing 500 ng/mL of MMC (AppliChem, Barcelona, Spain, CAS No.…”
Section: Cell Culturementioning
confidence: 99%
“…Whole-transcriptome sequencing (RNA-seq) and ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS/MS) are the modern high-throughput methods allowing for the identification of any signaling pathways determining the acquisition of certain phenotypes by cells in response to various stimuli. Resulting from RNA-seq, MMC-induced genotoxic stress in primary human coronary artery endothelial cells (HCAEC) and internal thoracic artery endothelial cells (HITAEC) leads to the upregulation of genes involved in the p53, GAS6/AXL, JNK/SAPK, PI3K/AKT, DNA damage, oxidative stress and inflammatory response signaling pathways, the inflammatory activation of endothelial cells, endothelial migration and differentiation, the adhesion of mononuclear blood fractions to the plasma membrane of endothelial cells and apoptosis, and to the downregulation of genes involved in angiogenesis [27]. At the same time, the proteomic profiling of the endothelial cells incubated under a genotoxic load has still not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that genotoxic stress induced by 6 h of exposure of endothelial cells to 500 ng/mL MMC is associated with proinflammatory activation of endothelium and endothelial dysfunction [ 17 , 18 , 19 ] underlying atherosclerosis [ 20 , 21 ], a leading cause of cardiovascular morbidity and mortality worldwide [ 22 , 23 ]. HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase inhibitors, also known as statins, are small molecules that are the rate-controlling enzyme of the mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%